2007
DOI: 10.3144/expresspolymlett.2007.53
|View full text |Cite
|
Sign up to set email alerts
|

Silane crosslinking of polyethylene: the effects of EVA, ATH and Sb2O3 on properties of the production in continuous grafting of LDPE

Abstract: Abstract. In this study, thermal, mechanical and fire retardant properties of silane-crosslinked low-density polyethylene (XLPE) containing ethylene-vinylacetate (EVA) copolymer, alumina trihydrate (ATH) and antimony trioxide (Sb2O3) have been studied. Samples were prepared in a single-screw extruder and the silane type was vinyltrimethoxy silane (VTMOS). Incorporation of ATH and Sb2O3 into polyethylene at sufficiently high loading introduces good fire retardancy expressed by limiting oxygen index (LOI). Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 21 publications
3
36
0
2
Order By: Relevance
“…The network structure makes the macromolecular LLDPE chain less flexible, thereby lowering the T c and making crystallization more difficult. Other researchers have also reported lower crystallinity in silane‐crosslinked samples [26–29]. Interestingly, the T c values of crosslinked LLDPE/PVA blends with ratios of 60/40 and 50/50 are close to that of the neat LLDPE.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…The network structure makes the macromolecular LLDPE chain less flexible, thereby lowering the T c and making crystallization more difficult. Other researchers have also reported lower crystallinity in silane‐crosslinked samples [26–29]. Interestingly, the T c values of crosslinked LLDPE/PVA blends with ratios of 60/40 and 50/50 are close to that of the neat LLDPE.…”
Section: Resultsmentioning
confidence: 54%
“…This finding suggests good interaction and adhesion between the two polymers. Several workers have reported that the addition of a coupling agent improved the interfacial adhesion through good wetting and by lowering the surface tension [20, 22, 24–28]. It is suggested that a similar mechanism operated in these silane/LLDPE/PVA blends, as described above.…”
Section: Resultsmentioning
confidence: 74%
“…However, to achieve desirable properties, a high loading of mineral fillers should be used which may lead to a dramatic decrease in mechanical properties and an increase of the density of the final product [4][5][6][7][8][9]. Also, the effect of aluminium hydroxide, antimony trioxide and EVA on the properties of silane crosslinked LDPE was investigated [10]. It has been reported that using layered silicates with large aspect ratios (a few nanometer thick but hundreds to thousands of nanometers long) in a polymer matrix improves mechanical properties [11][12][13], reduces thermal expansion coefficient [14], gas permeability [15] and flammability [16,17] of the polymer.…”
Section: Introductionmentioning
confidence: 99%
“…Easy processing, low cost and capital investments, and favourable properties of processed materials are the advantages of silane method [11]. Further studies on this subject would be found in literature for interested reader [12][13][14][15][16]. Considering the role of antioxidants in preventing or retarding oxidation degradation, it is important to study the proper type of antioxidant in crosslinked polyethylene which has no or the least interference with silane grafting reactions [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%